Assessment of Exhaust Gas Emission Impacts on Air Quality Surrounding PT PLN Nusantara Power, Nagan Raya - Samsidar, Samsidar; Ulhaq, Riza (SciencePlus, 2025)
Air pollution is an environmental issue that has a broad impact on human health and ecosystem balance. PT PLN Nusantara Power UP Nagan Raya as a coal-fired steam power plant (PLTU) has the potential to produce exhaust emissions that can reduce air quality in the surrounding area. This study aims to assess the impact of exhaust emissions on ambient air quality in organizations around the PLTU. The study uses a quantitative descriptive approach by measuring several air pollutant parameters, namely SO₂, NO₂, CO, O₃, NMHC, PM₁₀, PM₂.₅, and Pb at the UA-1 observation point located east of the PLN Nusantara Power, then compared with ambient air quality standards based on PP No. 22 of 2021. The measurement results show that all pollutant parameters are still below the national air quality standard threshold, including SO₂ <33.438 μg/m³, NO₂ <6.143 μg/m³, CO 2298.91 μg/m³, PM₁₀ 22.80 μg/m³, and PM₂.₅ 16.11 μg/m³. This indicates that at the time of the measurement, coal burning activities at the PLN Nusantara Power had not had a significant impact on air quality in surrounding organizations. However, continuous monitoring is still needed to ensure air quality remains safe and prevent potential long-term health risks.